Idiosyncratic Drug-induced Liver Injury: A Diagnosis Beyond Simplicity - Leong Hui Shan; Thirugnanasampanthar Terpari; Wahinuddin Sulaiman (Asian Journal of Medicine & Health Sciences, 2023)
Idiosyncratic drug-induced liver injury is a relatively uncommon adverse drug reaction but can be potentially fatal. The clinical spectrum of this liver disorder can range from an asymptomatic biochemical derangement to a life-threatening fulminant liver failure. Due to its unpredictable nature, the diagnosis of idiosyncratic drug-induced liver injury is challenging and demands a high index of suspicion. There is no definitive diagnostic marker and hence, it is mandatory to exclude other aetiologies of liver damage. While certain drugs are well-established to cause idiosyncratic hepatotoxicity, there remains a large group of agents which are yet to be identified as culprits. We report a case of probable idiosyncratic drug-induced liver injury that evolved after a tooth extraction in a young man in whom the diagnostic evaluation was complicated due to simultaneous exposure to multiple agents and incomplete information related to the drug.